Producing hogs under contract - Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Recently, there has been a renewed interest in contract hog production. Contractors are looking for an effective means to expand production or utilize excess feed production capacity. Producers enter contracts to minimize input cost and market risks or to obtain financing for buildings and equipment. Provisions vary from contract to contract. Producers that are making the decision whether to produce hogs under contract should calculate expected returns for a range of production and cost scenarios. Whatever the contract provisions, producers and contractors should make sure that the contract rewards them for what they do best.
Keywords: Swine; Contact; Program; Economics